Diagnosis of dampness in building conservation works. Case study: historical Fort Cornwallis, George Town, Penang / Al-Hafzan Abdullah Halim - Halim, Al-Hafzan Abdullah (2014)
Historic buildings have high value, particularly in architecture, history and past construction’s technology. Historic buildings usually experience physical defects like cracks, peeling paints, decays and others. The main factor that contributes to these defects is building dampness. Most decisions that have been made to overcome dampness are ad hoc decisions. By looking at the current situation there is no comprehensive scientific research in explaining the exact factor of dampness. Most of the scientific research done cannot be comprehended by contractors because the procedure used is ambiguous. As a result, faulty in the repair works will occur and lead to severe effects in which the same or even worse defects or damages can happen in the future. The goals of this study are to investigate the dampness problems on the historical buildings and to lay down a proper technique of analysis in dampness diagnosis. The method used in this study is a detailed observation, based on experimental qualitative research design. This research shows how the diagnosis of the dampness problems been carried out by using four stages approach to dampness investigation. It provides a detailed description of the four stages approach and applied it in the historical building. This research has gained an insight into a better understanding of dampness diagnosis and the result interpretation has been laid down in this research to confirm the causes of the dampness problem found from a case study. An understanding of the result is a vital part for the assessment because it will lead to the true diagnosis and investigation of the dampness problem in the historical building.